Utilizing Recorded English Dialogues in Teaching English Word Stress to Islamic Higher Education Students in Indonesia - Abdul Gafur Marzuki (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2019)
The objective of this study is to know the effectiveness of recorded English dialogues in developing the students understanding of English word stress for Islamic Education students. The study employed the classroom action research design. The subject of this study was undergraduate EFL students at the Islamic Education Department in 2018/2019 academic year. The data were collected through four research instruments: observation checklist, questionnaire, field notes, and test. The result of study shows that teaching English word stress through the utilizing recorded English dialogue performed by the researcher is effective to develop students understanding of English word stress. The primary criteria to judge that the students have development are that from the score they gained from two phases of test. In the first test, the students’ development reached 56.25%. Meanwhile, in the second test, students’ development attained 81.25%. Since learning achievement is calculated based on the number of students who get the target score, so it can be stated that the learning achievement has been attained.